Research at the Department of Physics and Astronomy - Fanelli, Duccio (Il Colle di Galileo, 2022)
The purpose of this brief contribution is to provide a concise description of the main directions of research currently being pursued at the Department of Physics and Astronomy of the University of Florence. In illustrating the various contributions, and without claiming to cover everything in the limited space available, we will follow a narrative path that covers the Department’s four macro-disciplinary areas (Theoretical Physics, Structure of Matter, Nuclear and Subnuclear Physics and Astrophysics).